Types and Distribution Characteristics of Callovian-Oxfordian Reservoir on the Right Bank of Amu Darya River in Turkmenistan - Qiang Wang (Geofluids)
Given the characteristics of significant or enormous resources, a wide range, many reservoir types, and challenging exploration on the right bank of the Amu Darya River, we systematically studied the characteristics of its reservoirs. Based on the core description, thin sections in combination with logging and seismic facies characteristics as well as regional tectonic-sedimentary background, the Callovian-Oxfordian platform and the gentle slope sedimentary system in the Amu Darya Basin of Turkmenistan were summarized. Sedimentary subfacies such as evaporation platform, restricted platform, open platform, and platform margin reef are developed in block A and its west. In contrast, the upper slope, lower slope, and basin sedimentary subfacies are developed in the east of block A. On this basis, the main reservoir types on the right bank of the Amu Darya River are summarized, namely, porous reservoir, vuggy reservoir, fractured-porous reservoir, and fractured-vuggy reservoir. After describing the characteristics of various reservoirs in detail, the main controlling factors, development patterns, and distribution rules of the development of different reservoirs are summarized. Specifically, based on the platform reef, the porous reservoir and vuggy reservoirs are developed mainly on the concealed palaeouplift in the study area and are greatly influenced by atmospheric freshwater leaching and buried dissolution. Based on the dominant sedimentary facies, the fractured-porous reservoirs are mainly developed in the central areas on the right bank of the Amu Darya River. In the later period, hydrothermal fluid and hydrocarbon-generating acidic fluid can dissolve the reservoir through strike-slip faults and their associated fractures. Diagenetic fluid enters the reef through faults and associated fractures to form dissolved reservoir bodies of a certain scale. The fractured-vuggy reservoirs are mainly controlled by faults and dissolution and are mainly developed near the eastern thrust fault on the right bank of the Amu Darya River, effectively guiding the direction for further exploration and development in this area.